EV duty vehicles: Features and functions of ciliary extracellular vesicles - Vinay, Ludovic; Belleannée, Clémence (Frontiers in Genetics, 2022)
The primary cilium is a microtubule-based organelle that extends from a basal body at the surface of most cells. This antenna is an efficient sensor of the cell micro-environment and is instrumental to the proper development and homeostatic control of organs. Recent compelling studies indicate that, in addition to its role as a sensor, the primary cilium also emits signals through the release of bioactive extracellular vesicles (EVs). While some primary-cilium derived EVs are released through an actin-dependent ectocytosis and are called ectosomes (or large EVs, 350–500 nm), others originate from the exocytosis of multivesicular bodies and are smaller (small EVs, 50–100 nm). Ciliary EVs carry unique signaling factors, including protein markers and microRNAs (miRNAs), and participate in intercellular communication in different organism models. This review discusses the mechanism of release, the molecular features, and functions of EVs deriving from cilia, based on the existing literature.